Effect of Caryodendron orinocense on dry matter degradation - Losada Aguilar, Pablo; Cuesta Peralta, Aurora; Vargas Martínez, Juan de Jesús (Agronomía Mesoamericana, 2017)
The objective of the present study was to evaluate the in vitro and in situ dry matter degradation by including cacay cake (Caryodendron orinocense) on a diet based on Brachiaria dictyoneura. The experiment was developed in an animal nutrition laboratory on the Animal Sciences Faculty at the Universidad de Ciencias Aplicadas y Ambientales, Bogotá, Colombia, in July 2015. Four treatments were evaluated: B. dictyoneura, cacay cake and two mixtures of B. dictyoneura: cacay cake (80:20 and 60:40). The chemical composition and the in vitro and in situ degradability of the dry matter and the crude protein, at 48 hours were determined. The variables were analyzed through a complete randomized design with four treatments. The inclusion of cacay cake decreased the cell wall-associated with carbohydrate concentration and increased the higher digestibility nutrients; the crude protein and dry matter, in situ and in vitro degradability increased 22, 6 and 38%, respectively. In conclusion, the inclusion of cacay cake on a diet of B. dictyoneura improves dry matter degradation in vitro and in situ conditions.